Simulation study of joint trans-dimenstional bayesian inversion of scattering and reflection data - Steininger, Gavin; Dettmer, Jan; Holland, Charles W.; Dosso, Stan E. (Canadian Acoustics, 2012)
A joint trans-dimensional (trans-D) Bayesian inversion approach is developed and is applied to synthetic seabed scattering and reflection data to determine the ability of such data to resolve geoacoustic and scattering parameters. Bayesian inversion requires specifying the posterior probability density (PPD), and a method to sample PPD. To adequately approximate the PPD 600,000 models were sampled from it using the rjMCMC algorithm. These are thinned by one third to reduce sample correlation; only these remaining samples are considered here. The one- and two-dimensional marginal distributions of the scattering parameters for the inversion are found. The parameter distributions are found to be centered near the true values, and the uncertainties indicate a useful level of resolution of the roughness spectrum. Geoacoustic parameters are also well resolved, but are not shown here due to space constraints.